2022
DOI: 10.1093/cercor/bhac153
|View full text |Cite
|
Sign up to set email alerts
|

Organization and engagement of a prefrontal-olfactory network during olfactory selective attention

Abstract: Background Sensory perception is profoundly shaped by attention. Attending to an odor strongly regulates if and how it is perceived – yet the brain systems involved in this process are unknown. Here we report integration of the medial prefrontal cortex (mPFC), a collection of brain regions integral to attention, with the olfactory system in the context of selective attention to odors. Methods First, we used tracing methods to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 158 publications
1
10
0
Order By: Relevance
“…In Huntington’s disease, as the disease progresses, the greatest changes appear to be in the less cognitively demanding tests, specifically in the time taken to recite colour names and words read, i.e., the congruent test ( Snowden et al, 2001 , Ho, 2003 ). An explanation for this could be that information processing speed and recitation of automatic over-learned sequences deteriorates as the disease progresses, which is thought to involve a striatal contribution ( Cansler, 2023 ) Therefore, the data from this study shows that the striatum may be globally important for performance in the rRCT task, which may explain why altered Zif268 expression in the DMS was observed in both the rRCT Congruent and Incongruent groups, albeit that lower expression was actually associated with greater accuracy. However, further validation of the roles of the IL, DMS and RSCb in response confliction are required via lesion or inactivation studies.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In Huntington’s disease, as the disease progresses, the greatest changes appear to be in the less cognitively demanding tests, specifically in the time taken to recite colour names and words read, i.e., the congruent test ( Snowden et al, 2001 , Ho, 2003 ). An explanation for this could be that information processing speed and recitation of automatic over-learned sequences deteriorates as the disease progresses, which is thought to involve a striatal contribution ( Cansler, 2023 ) Therefore, the data from this study shows that the striatum may be globally important for performance in the rRCT task, which may explain why altered Zif268 expression in the DMS was observed in both the rRCT Congruent and Incongruent groups, albeit that lower expression was actually associated with greater accuracy. However, further validation of the roles of the IL, DMS and RSCb in response confliction are required via lesion or inactivation studies.…”
Section: Discussionmentioning
confidence: 72%
“…Finally, it is worth noting the medial prefrontal cortex is highly integrated with the olfactory system ( Cansler, 2023 ). Thus, it is possible that IEG activation in the medial prefrontal cortex could be induced through attending to olfactory guidance cues.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we recorded mPFC field potential rhythms from a subset of rats used in the behavioral dataset ( n = 3) to see if mPFC rhythms tracked any aspects of behavioral context formation that we were able to define (see Figure 7 for approximate recording locations and field potential examples). We examined three mPFC rhythms, each suggested to have a role in linking cognition to behavior in rodents; 1) the theta rhythm (6 – 12 Hz), which tends to synchronize with hippocampal theta when spatial working memory is taxed (Benchenane et al ., 2010; de Mooij-van Malsen et al ., 2023; Hallock et al ., 2016; Hyman et al ., 2010; Jones & Wilson, 2005; Negrón-Oyarzo et al ., 2018; Stout et al ., 2023; Tavares & Tort, 2022); 2) the beta rhythm (15 – 30 Hz), which tends to be present during decision-making (de Mooij-van Malsen et al ., 2023; Jayachandran et al ., 2023; Symanski et al ., 2022); and 3) the gamma rhythm (40 – 100 Hz), which has been associated with working memory, learning, and sensory information processing (Cansler et al ., 2022; de Mooij-van Malsen et al ., 2023; Negrón-Oyarzo et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The prefrontal cortex (PFC) plays an important role in this process. Recent evidence suggests that the PFC has dedicated neural networks that receive input from olfactory regions, and that the activity of these networks is coordinated on the basis of selective attention producing different brain alert states [49].…”
Section: Olfactionmentioning
confidence: 99%
“…Bottom-up automatic activation may generate supraliminal brain signals, or representational contents with weak adaptive weights, as a candidate mechanism to explain how the brain manages to subliminally process perceptual input [60] that is either not directly relevant at a given moment in time, or cannot be made available to conscious processing because of a local brain lesion [59]. Grossberg [9,12,17,19] suggested that bottom-up activation may automatically activate target cell populations at higher levels of processing, as in bottom-up activation of the PCF by sensory cortices [47,49], for example.…”
Section: Bottom-up Automatic Activationmentioning
confidence: 99%